KEMAMPUAN PERTUMBUHAN BERAT BADAN TERNAK DOMBA DENGAN 125 132 PEMBERIAN PAKAN JERAMI PADI DENGAN PERLAKUAN NATRIUM HIDROK-SIDA (NAOII) SEBAGAI PENGGANTI HIJAUAN - Bharoto, Bharoto (Jurnal Ilmu-Ilmu Pertanian, 2005)
This research was aim to discover weight growth ability of fat tailed sheep livestock which feeds ice straw that was treated by hydroxide alkali ( NaOH). This research was using 10 sheep under 1 year aged which was divided into two groups, per group consist of 5 sheep with average weight was 14 kg for first group and 13.97 kg for second group. Feed treatment for first group was chopped dry rice straw plus NaOH with ratio 2 grams NaOH for 100 grams dry rice straw. Previously, NaOH was dissolved into 600 ml of water then sprayed to the straw till homogenous. Second group was for control, fed with verdant big grass (Pennisentum purpureum). Both of those groups fed with suplement -food called bekatul (rice bran). It quantity was 400 grams per sheep per day. Research was done during 90 days. Data which was taken covering weight increasing and amount of food consumption per sheep per day. The research result showed average of weight increasing for first group was 32.8 grams and the second group was 45.5 grams per sheep per day. Amount of dry water feed consumption per sheep per day (rice bran grasses) for first group was 0.428 kg and for second group was 0.693 grams. Amount of digestible protein consumption and digestible energy per sheep per day for each group was 24.31 grams and 1.299 mcal for first group then 35.32 grams and 2.014 mcal for second group. Therefore weight increasing, amount of consumption (dry matter digestible protein, digestible energy) of second group was better than first group (P < 0,05). Keyword : , ,